Associations Among Childhood Threat and Deprivation Experiences, Emotion Dysregulation, and Mental Health in Pregnant Women - Greene, Carolyn A. (Psychol Trauma, 2021)
OBJECTIVE: Women who have experienced childhood maltreatment are at increased risk for experiencing mental health problems. When these occur during pregnancy, they are associated with birth complications and worse developmental outcomes for children. Emotion dysregulation (ED) may be an important, and potentially modifiable, mechanism that links women’s maltreatment experiences with their mental health. However, there is limited information about the emotion regulation skills of pregnant women to guide treatment. The current study examines the unique effects of childhood threat (physical, sexual, and emotional abuse and exposure to violence) and deprivation (physical and emotional neglect and separation from primary caregivers) experiences on pregnant women’s ED, posttraumatic stress and negative emotional symptoms, and social support. METHOD: 243 women were recruited from an urban prenatal care clinic, the majority of whom identified as Latinx (80%) and low-income (90%). The mean age of the women was 27 years (SD = 5.5). RESULTS: Structural Equation Modeling revealed significant indirect pathways from childhood threat experiences to posttraumatic stress and negative emotional symptoms via women’s ED. In contrast, childhood deprivation experiences were associated with inattention to one’s emotions and low perceived social support. CONCLUSIONS: These results underscore the importance of identifying women during pregnancy who may be at risk for ED or emotional inattentiveness due to childhood maltreatment experiences and providing prevention and intervention efforts aimed at enhancing their emotional awareness and regulation.